Pengaruh Penerapan Media Pembelajaran Audio Visual terhadap Hasil Belajar Siswa pada Mata Pelajaran Ilmu Pengetahuan Alam dan Sosial (IPAS) Kelas III di SD Islam Faaz Tuban Tahun Pelajaran 2024/2025 - Hamid, Abdul (Madrasah Ibtidaiyah Education Journal, 2025)
This research aims to determine the effect of applying audio-visual learning media on student learning outcomes taught in the science and social sciences subjects at Faaz Tuban Islamic Elementary School in Class III. The problem of this research is the low student learning outcomes in science subjects. The research carried out in this research is research pre-test in a post-test using two classes. The sample for this research was class III A (experimental) with 16 students using audio-visual media and class III B (control) with 16 students using traditional teaching methods. An essay test with 5 questions was used as a research instrument. Based on the average calculation, the final average score of students in the experimental class, which used audio-visual learning materials, was 88.33, and the final average score of students in the control class, which used the traditional learning model, was 72.72, the medium criteria. This research was tested using the t-test to obtain hypothesis results. From the results of data hypothesis testing, it can be concluded that the learning outcomes of students who use audio-visual media in science and science subjects are higher compared to learning that uses traditional learning methods in class III of SD Islam Faaz Tuban for the 2024/2025 academic year